Effects of fine particle migration caused by one wetting-drying cycle on desiccation micro-cracks in intact loess - Zhi-yuan He; Peng-hui Ma; Qing-yi Mu; Chao Zhou; Ke Mu; Zhi-jie Jia; Jian-bing Peng (Engineering Geology, 2026)

Variable silicate weathering and enhanced reverse weathering during the Ordovician-Silurian transition - Xiangrong Yang; Detian Yan; Denglin Han; David J. Wilson; Philip A.E. Pogge von Strandmann; Xianyi Liu; Chun-Yao Liu; Ke Xu; Can Chen; Mu Liu; Daizhao Chen (Geochimica et Cosmochimica Acta, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

A modified SLD-ESD model for characterizing and predicting supercritical CH4 adsorption on shale at wide temperatures and pressures - Ke Hu; Chunkui Mu; Zhaolong Ge; Xiang Ao (Fuel, 2026)

The transformation of Ca/Mg-silicate to Co/Ni/Fe-silicate in biomass carbon from gourd leaves for supercapacitors - Shaoqing Zhang; Xiang Ke; Tianming Lv; Jiqi Zheng; Yang Mu; Xuchun Wang; Miao Cui; Teng Du; Changgong Meng (Chemical Engineering Journal, 2026)

Organic association of U, Mo, V, and Ni in Neogene coals from the Puyang Mine, Yunnan, southwestern China - Zhenyu Xu; Xingxing Guo; Xiaomei Wang; Haoran Yang; Ke Sheng; Yuanhe Mu; Xingwang Ren; Baoqing Li (International Journal of Coal Geology, 2026)

Seawater pH fluctuations during the Ordovician to Silurian transition: Insights from δ11B records in carbonates - Xiangrong Yang; Shaojie Li; Detian Yan; Yue Cai; Denglin Han; Ke Xu; Yanqing Li; Can Chen; Peng Sun; Mu Liu; Chunyao Liu; Daizhao Chen (Global and Planetary Change, 2026)

Distinct and interactive effects of multiple consumers on plant trade‐offs and diversity in alpine meadows - Yimin Zhao; Peng Zhang; Junsheng Ke; Yilin Dang; Kui Hu; Zijian Yu; Hongying Jiang; Chenrui Wang; Wenjie Li; Jing Zhang; Dong Zhang; Xue Zhang; et al. (Ecology, 2026)
Plants face a fundamental trade‐off between acquiring resources for growth or interspecific competition and simultaneously investing in anti‐consumer defenses. These selective pressures shape species' life history strategies and promote stable coexistence. However, the specific roles of distinct consumer groups, particularly the often‐overlooked oomycetes, in driving growth–defense trade‐offs and sustaining plant diversity remain poorly understood. To this end, we conducted a factorial field experiment in an alpine meadow on the Qinghai‐Tibetan Plateau, manipulating the nitrogen supply (to test resource acquisition effects) and removing consumer groups (i.e., mammalian herbivores, fungi, and oomycetes) both individually and in combination. We used standardized major axis regression to investigate how plant species differentially allocate resources between growth, competition, and defense, and how such trade‐offs influence plant species diversity. Species' responses to nitrogen addition and consumer removal were positively correlated, supporting the existence of widespread growth–defense trade‐offs. The strength of this trade‐off varied significantly among consumer removal treatments, with fungi and herbivores exerting stronger effects than oomycetes. The removal of both herbivores and oomycetes amplified their individual impacts on plant growth–defense trade‐offs. Consistent with this pattern, the removal of fungi or herbivores, but not oomycetes, led to pronounced declines in plant diversity. Our findings reveal the divergent roles of individual consumer groups in shaping plant life history strategies and highlight that cross‐trophic interactions, particularly those involving herbivores or fungal pathogens, are critical for maintaining plant diversity.

Mycotoxin deoxynivalenol drives antibiotic resistance evolution in Bacillus cereus via cell wall remodeling, compromising clinically critical antibiotics - Fengru Deng; Linyu Ke; Mi Huang; Meichan Chen; Zhongsong Chen; Peiqiang Mu; Mengzhuo Shi; Jun Wu; Yiqun Deng (Journal of Hazardous Materials, 2026)

Bimetallic metal-organic frameworks with hydrolytic esterase activity applied to mycotoxin decontamination - Ke Cheng; Peiheng Dina; Fei Yu; Yinghui Zhang; Yunpeng Wang; Wenjing Mu; Xiuguo Wang (Chemical Engineering Journal, 2026)

Phaeovulum Molybdatiresistens sp. nov., a Molybdate-resistant Bacterium Isolated from Eutrophic Pond Water - Jianjun Song; Yuanshuo Qiu; Ke Ma; Yuelin Liu; Jia Wang; Yaqi Liu; Xiaolong Song; Kaiyue Wang; Jinhua Hu; Weidong Mu; Yanfang Zhao; Aijv Liu; et al. (Current Microbiology, 2026)

Biodegradation of unpretreated polypropylene microplastic and agricultural polypropylene film by a bacterium isolated from an oil reservoir - Sheng Jin Li; Yun Yang Wan; Zhe Ke Zhong; Ying Jia Zhu; Hong Mei Mu; Sheng Bao Shi (Journal of Environmental Chemical Engineering, 2025)

Safety, probiotic, and functional properties of yeasts with high proteolytic activity screened from Chinese traditional fermented dairy products - Ke Qu; Siyi Li; Guangqing Mu; Shujuan Jiang (Food Bioscience, 2025)

Prediction strategy and full-scale validation of ship main engine energy consumption considering the influence of ocean currents - Ke Yang; Changxuan Mu; Limin Huang; Zhen Yang; Guihua Xia (Ocean & Coastal Management, 2025)

Exploring Allium mongolicum Regel flavonoids alleviation of deoxynivalenol-induced gut inflammation and flesh-quality improvement based on muscle-intestinal axis in a Channa argus model - Zhe Yu; Zhuang Xiong; Yi Wang; Zhi-Qiang Gao; Ke-Xin Lu; Ying Zhang; Mu-Yang Li; Yuan-Xi Yue (Food Bioscience, 2025)

Modes of occurrence of rare earth elements and yttrium in bituminous coals with different ranks from the Hedong Coalfield, northern China - Zhenyu Xu; Xiaomei Wang; Fan Deng; Xingxing Guo; Yuxuan Han; Ke Sheng; Yuanhe Mu; Qin Yang (International Journal of Coal Geology, 2025)

Triple microenvironment synergy engineering by grain boundaries of hydrophilic Cu electrode for boosting low-concentration nitrate electroreduction - Xin Wang; Qinian Wang; Mu Yuan; Xu Cheng; Bo Zhang; Ke Zhang; Lili Wang; Chao Wu; Xing Zhang (Chemical Engineering Journal, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Insights into the interlinkages between rhizosphere soil extracellular enzymes and microbiome assemblages across soil profiles in grasslands - Xueqing Liu; Xifeng Fan; Mingcai Zhang; Hui Zhang; Yuesen Yue; Juying Wu; Wenjun Teng; Na Mu; Ke Teng; Haifeng Wen (Applied Soil Ecology, 2025)

The emulsion-filled gels with different fat contents exhibit various friction behavior and dynamic fat-related texture perception at different temperatures - Yueji Zeng; Sihan Zhang; Ke Fan; Shuo Mu; Yang Luo; Linlin Wang; Xiankang Fan; Fuqing Wang; Ran Wang; Jie Luo (Food Quality and Preference, 2025)

Specific glycomacropeptide detection via polyacrylamide gel electrophoresis with dual imaging and signal-fusion deep learning - Yiren Cao; Youli Tian; Ke-Er Chen; Yixin Ma; Qiang Zhang; Weiwen Liu; Zhishen Mu; Shengpeng Su; Chengxi Cao (Food Chemistry, 2025)

Polymer-derived C-Sn/SnO2@rGO heterostructures with dual assistance of gallic acid for high-performance lithium-ion batteries - Guanwen Wang; Baoyi Mu; Ke Cao; Chunlei Chi; Chuanqing Wang; Chao Huangfu; Fan Feng; Bin Qi; Qiushi Miao; Xinhou Yang; Zheng Liu; Tong Wei; et al. (Chemical Engineering Journal, 2025)

Adaptive biodegradation and mechanism study of volatile chlorinated aromatic hydrocarbons in landfill cover soil bioreactor zone - Jianhua Yuan; Baozhong Mu; Yuehui Xia; Hao Zhang; Liangjie Li; Zhilin Xing; Xihong Ke (Environmental Research, 2025)

Application of a thermo-mechanical-damage coupling model based on the TLF-SPH in the thermal cracking simulation of brittle solids - Dianrui Mu; Ke Zhang; Kesheng Jin; Shuai Zhao; Xiao Wang (Computers and Geotechnics, 2025)

An optimized non-landslide sampling method for Landslide susceptibility evaluation using machine learning models - Shuai Xu; Yingxu Song; Pin Lu; Guizhen Mu; Ke Yang; Shangxiao Wang (Natural Hazards, 2025)

Dimeric PD-L1 specific affibody grafted Fe-based nanosheets for tumor-targeting dual-mode magnet resonance imaging and enhancement of Photothermal-Immunotherapy - Xinyu Zhang; Hui Liu; Chenyu Wang; Yuan Gao; Shiqi Zhao; Mengyao Mu; Ke Ren; Yufang Gong; Qing Fan; Xiao Sun (Chemical Engineering Journal, 2025)

Temperature and microbial metabolic limitations govern microbial carbon use efficiency in the Tibetan alpine grassland - Xuejun He; Fangbin Liu; Tian Ma; Ase Ma; Yaoyao Wang; Yifan Li; Wenjing Gao; Zhiying Yang; Junsheng Ke; Yao Xiao; Li Zhang; Mu Liu; et al. (Applied Soil Ecology, 2025)

Design of a diblock-based membraneless organelle system for metabolic process control - Juntao Ke; Li Wan; Maiqi Chen; Yizheng Lv; Yuanlin Liu; Yingying Zhu; Wenli Zhang; Wanmeng Mu (Chemical Engineering Journal, 2025)

Digital one-pot SHERLOCK assisted superfast and reverse transcription free method for circulating microRNA absolute quantification - Zheyu Zou; Juxin Yin; Liping Xia; Weihong Yin; Ke Liu; Yating Pan; Kai Hu; Yehong Gui; Jianjian Zhuang; Duo Xiao; Ying Mu (Chemical Engineering Journal, 2025)

Overcoming radiation-induced PD-L1 upregulation by novel gadolinium-palladium nanoplatforms for enhanced tumor radio-immunotherapy - Kai Guo; Hui Liu; Mengmeng Zhang; Nengyi Ni; Mengyao Mu; Ke Ren; Jiahui Chen; Qing Fan; Xueli Xu; Xiao Sun; Ximing Wang (Chemical Engineering Journal, 2025)

Boosting bioelectricity generation in bioelectrochemical systems with nitrogen-doped three-dimensional graphene aerogel anode - Yi-Xuan Wang; Xiao-Li Liu; Wen-Qiang Li; Yi-Ran Wang; Ke-Wan Li; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

A nucleus-targeting fluorescence probe for rapid diagnosis of colorectal cancer - Yonggan Xue; Jimei Chi; Bobin Ning; Lijun Cheng; Wenchen Wang; Qingyu Meng; Liang Huang; Mu Ke; Sen Li; Meng Su; Baoqing Jia (Chemical Engineering Journal, 2024)

Experimental Study on Mechanical Behavior, Fracture Characteristics, and Acoustic Emission Damage Characteristics of Sandstone Under Triaxial Multistage Stress Disturbance - Sheng-Qi Yang; Jing Yang; Zong-Long Mu; Guang-Jian Liu; Man Huang; Ke-Sheng Li; Yan-Hua Huang (Rock Mechanics and Rock Engineering, 2024)

A gas-mechanical-damage coupling model based on the TLF-SPH method and its application to gas seepage in fractured coal - Dianrui Mu; Qing Ma; Ke Zhang; Jiyuan Zhao (Computers and Geotechnics, 2024)

Transcriptomic and physiological analysis provide new insight into seed shattering mechanism in Pennisetum alopecuroides ‘Liqiu’ - Yue Xu; Lingyun Liu; Ming Jia; Ke Teng; Na Mu; Yidi Guo; Muye Liu; Juying Wu; Wenjun Teng; Linkai Huang; Xifeng Fan; Yuesen Yue (Theoretical and Applied Genetics, 2024)

Intelligent Dynamic Warning Method of Rockburst Risk and Level Based on Recurrent Neural Network - Shichao Zhang; Chaomin Mu; Xianhui Feng; Ke Ma; Xiao Guo; Xinsheng Zhang (Rock Mechanics and Rock Engineering, 2024)

A MYB transcription factor GhTT2 of Gossypium hirsutum regulates proanthocyanidin accumulation and improves osmotic tolerance in Arabidopsis - Jun Mei; Rongrong Mu; Qingqing Niu; Huimin Zhu; Ruoxi Chen; Xiaomiao Cai; Meng Miao; Dongliang Yu; Liping Ke; Yuqiang Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Contrasting roles of fungal and oomycete pathogens in mediating nitrogen addition and winter grazing effects on biomass - Peng Zhang; Mengjiao Huang; Chaorui Chen; Kui Hu; Junsheng Ke; Mu Liu; Yao Xiao; Xiang Liu (Ecology, 2024)
Both bottom‐up and top‐down processes modulate plant communities. Fungal and oomycete pathogens are most common in global grasslands, and due to differences in their physiology, function, host range, and life cycles, they may differentially affect plants (in both intensity and direction). However, how fungal and oomycete pathogens regulate bottom‐up and top‐down effects on plant community biomass remains unclear. To this end, we conducted a 3‐year field experiment in an alpine meadow incorporating mammalian herbivore exclosure, fungicide/oomyceticide application, and nitrogen addition treatments. We arranged 12 blocks with half randomly assigned to be mammalian herbivore exclosures (fenced to exclude grazing sheep), and the other half were fenced most of the year but not in winter (winter grazing control). Six 2.5 × 2.5 m square plots were established in each block, with each of the six plots assigned as control, nitrogen addition, fungicide application, oomyceticide application, nitrogen addition + fungicide application, and nitrogen addition + oomyceticide application. We found that fungicide application significantly increased plant community biomass (mainly Poaceae species) under nitrogen addition and promoted the bottom‐up effect of nitrogen addition on plant community biomass by altering the community‐weighted mean of plant height (via species turnover). Meanwhile, oomyceticide application significantly increased plant community biomass (mainly Poaceae species) when mammalian herbivores were excluded and weakened the top‐down effect of winter grazing on plant community biomass by driving intraspecific variation in plant height. Our results highlight that fungal and oomycete pathogens play important (but differing) roles in mediating the effects of nutrient availability and higher trophic levels on plant community biomass. Mechanistically, we demonstrated that plant pathogen‐related modulation of plant community biomass is achieved by alterations to plant height. Overall, this study combines both community and disease ecology to reveal complex interactions among higher trophic levels and their potential impacts on terrestrial ecosystem functioning under human disturbance.

Occurrence of polyhalogenated carbazoles and the combined effects with heavy metals on variation in bacterial communities in estuarine sediments - Shanmin Hu; Minggang Zheng; Yingdi Mu; Aifeng Liu; Yuqing Jiang; Ying Li; Ke Ning; Ling Wang (Marine Pollution Bulletin, 2024)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

Analyzing the cellular and molecular atlas of ovarian mesenchymal cells provides a strategy against female reproductive aging - Longzhong Jia; Wenji Wang; Jing Liang; Shudong Niu; Yibo Wang; Jian Yang; Lingyu Li; Ge Wang; Xueqiang Xu; Lu Mu; Kaixin Cheng; Xuebing Yang; et al. (Science China Life Sciences, 2023)

Fibrillarin promotes homologous recombination repair by facilitating the recruitment of recombinase RAD51 to DNA damage sites - Yanhua Mu; Jinhua Han; Mingjie Wu; Zongfang Li; Ke Du; Yameng Wei; Mengjie Wu; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2023)

Residue dissipation dynamics and dietary risk assessment of emamectin benzoate, chlorantraniliprole, chlorfenapyr, and lufenuron in cabbage - Xiaoyao Wang; Shuai Hu; Lingtao Meng; Kai Wang; Xianxia Zhang; Ke Li; Ning Wang; Nan Zou; Yue Xu; Beixing Li; Wei Mu; Xiuyu Pang (Environmental Science and Pollution Research, 2023)

Plant and soil responses to grazing intensity drive changes in the soil microbiome in a desert steppe - Zhen Wang; Shenyi Jiang; Paul C. Struik; Hai Wang; Ke Jin; Riliga Wu; Risu Na; Huabing Mu; Na Ta (Plant and Soil, 2023)

Prenatal PM2.5 exposure increases the risk of adverse pregnancy outcomes: evidence from meta-analysis of cohort studies - Wanrong Wang; Siqi Mu; Weizhen Yan; Naiyu Ke; Han Cheng; Rui Ding (Environmental Science and Pollution Research, 2023)

Organic matter preservation conditions in the third member of the Shahejie Formation (Dongpu Depression, China) - Xiuyan Liu; Honghan Chen; Xiaoshui Mu; Hongan Zhang; Junjia Fan; Yahao Huang; Ke Zhao; Ahmed Mansour; Thomas Gentzis; Mehdi Ostadhassan (International Journal of Coal Geology, 2023)

Ecotoxicological risk assessment of 14 pesticides and corresponding metabolites to groundwater and soil organisms using China-PEARL model and RQ approach - Jiangong Jiang; Zhixin Liu; Beixing Li; Shankui Yuan; Ronghua Lin; Xin Yu; Xiao Liu; Xianxia Zhang; Ke Li; Dong Xiao; Shaoli Yu; Wei Mu (Environmental Geochemistry and Health, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Modification of sedimentation and bioaccumulation behavior as an efficient strategy to modulate the toxicity of pyraclostrobin to zebrafish (Danio rerio) - Aiping Wang; Yue Sun; Zhengyi Sun; Xiao Liu; Xin Yu; Ke Li; Xianxia Zhang; Yue Xu; Wei Mu; Beixing Li (Environmental Pollution, 2023)

Geographical distance, host evolutionary history and diet drive gut microbiome diversity of fish across the Yellow River - Baozhu Pan; Xu Han; Ke Yu; He Sun; Rong Mu; Chun‐Ang Lian (Molecular Ecology, 2023)
Fish represent a large part of the taxonomic diversity of vertebrates and are of high commercial value. However, the factors influencing the gut microbiota composition of freshwater fish over large spatial scales remain unclear. Therefore, this study explored gut microbiome diversity in 24 fish species from the Yellow River, which spans over 1500 km across China. The results showed that geographical distance, host phylogeny and diet significantly influenced gut microbial community diversity, whereas sex, body length and body weight had minimal influence. Geographical distance was the primary factor shaping gut microbiota, and dissimilarity in microbial community structure increased with an increase in geographical distance, which was mainly driven by dispersal limitation. The microbial communities were more homogeneous at higher host taxonomic resolutions due to the dominant role of homogeneous selection in community convergence. Phylosymbiosis was observed across all host species, with a stronger pattern in Cypriniformes, which harbour host‐specific microbial taxa. Host diet explained little variation in gut microbiome diversity, although it was significant for all diversity metrics tested. These findings collectively suggest that the geographical and host‐based patterns of fish gut microbiota tend to be shaped by different ecological forces across the Yellow River. The present work provides a robust assessment of multiple factors driving fish gut microbial community assembly and offers insight into the mechanisms underlying shifts in fish gut microbiota in rivers across large spatial scales.

High-performance aggregation-induced emission active poly(ether sulfone)s as polymeric electret for energy-saving genuine photonic transistor memory - Chun-Yao Ke; Mu-Huai Chen; Guey-Sheng Liou (Chemical Engineering Journal, 2023)

Neural Mechanism Underlying Task-Specific Enhancement of Motor Learning by Concurrent Transcranial Direct Current Stimulation - Ying Wang; Jixian Wang; Qing-Fang Zhang; Ke-Wei Xiao; Liang Wang; Qing-Ping Yu; Qing Xie; Mu-Ming Poo; Yunqing Wen (Neuroscience Bulletin, 2023)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Identification and functional analysis of a pollen fertility-associated gene GhGLP4 of Gossypium hirsutum L. - Hongli Zheng; Rongjia Wang; Qimeng Jiang; Diandian Zhang; Rongrong Mu; Yihan Xu; Vitalis E. Nnaemeka; Jun Mei; Yanyan Zhao; Fangfang Cai; Dongliang Yu; Yuqiang Sun; et al. (Theoretical and Applied Genetics, 2021)

Transient silencing of VvCSN5 enhances powdery mildew resistance in grapevine (Vitis vinifera) - Kai-Cheng Cui; Min Liu; Gui-Hua Ke; Xing-Yuan Zhang; Bo Mu; Min Zhou; Yang Hu; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Hyperprogressive disease in patients with advanced renal cell carcinoma: a new pattern of post-treatment cancer behavior - Zhong Zheng; Ke Wu; Zhixian Yao; Xingyu Mu; Hantao Wu; Weiguang Zhao; Leilei Cheng; Zhihong Liu (Immunologic Research, 2020)

Identification and characterization of the Bacillus atrophaeus strain J-1 as biological agent of apple ring rot disease - Yangping Mu; Ying Yue; Guirong Gu; Yiming Deng; Hong Jin; Ke Tao (Journal of Plant Diseases and Protection, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Pedobacter pollutisoli sp. nov., Isolated from Tetrabromobisphenol A-Contaminated Soil - Yang Mu; Zhuang Ke; Chen-Xi Feng; Xiao-Wei Wang; Xiao-Wen Wang; Hong-Mei Wang; Qing Chen; Jian He (Current Microbiology, 2019)

Isolation and functional characterization of the SpCBF1 gene from Solanum pinnatisectum - Wenjiao Zhu; Ke Shi; Ruimin Tang; Xiaoying Mu; Jinghui Cai; Min Chen; Xiong You; Qing Yang (Physiology and Molecular Biology of Plants, 2018)

Seasonal Variation of CO2 Vertical Distribution in the Atmospheric Boundary Layer and Impact of Meteorological Parameters - Koorosh Esteki; Neeraj Prakash; Yanli Li; Chao Mu; Ke Du (International Journal of Environmental Research, 2017)

Methylenebisnicotiflorin: a rare methylene-bridged bisflavonoid glycoside from ripe Pu-er tea - Mu-Ke Tao; Min Xu; Han Zhang; Hui Chen; Chang Liu; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Ying-Jun Zhang (Natural Product Research, 2016)

Cloning and expression of a wild eggplant cytochrome P450 gene, StoCYP77A2, involved in plant resistance to Verticillium dahliae - Liu Yang; Ce Shi; Xiaoying Mu; Chao Liu; Ke Shi; Wenjiao Zhu; Qing Yang (Plant Biotechnology Reports, 2015)

Safety and efficacy study of lung cancer stem cell vaccine - Mao Lin; Shu-Ying Li; Ke-Cheng Xu; Zheng-Ping Liu; Feng Mu; Yuan-Ying Yuan; Xiao-Hua Wang; Ji-Bing Chen; Qiao Li (Immunologic Research, 2015)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Plants interactions between Suaeda salsa individuals are mediated by salinity stress - Hao Zhang; Jian-Na Li; Gen-Xuan Wang; Xin-Feng Dai; Mu-Qing Qiu; Ke-Feng Zheng (Acta Physiologiae Plantarum, 2007)